Monitoring of home recovery using the 317-nursing mobile application following day-case surgery in children: Perspectives from both nurses and patients. Issue 31 (August 2019) - Li, Canping; Huang, Shoujiang; Su, Xiaohua; Zhang, Tingting; Jiang, Kewen
Abstract : Abstract: The number of elective day-case surgeries has considerably increased in recent years, especially in China. Few studies have investigated the ability of mobile applications to assist recovery for patients having undergone day-surgery; however, these studies have indicated that the use of mobile applications is cost-efficient and has a positive effect on recovery after surgery. This study aimed to evaluate the utility and efficacy of using the 317-nursing mobile application program (317NAPP) for monitoring home recovery following day-surgery involving high ligation of the hernial sac in pediatric patients. Prospective clinical study involving 2 parallel groups. Patients were randomly divided into the "intervention 317NAPP group" (n = 64) and the control group (n = 63). Patients were followed-up using the 317NAPP in the intervention group and via telephonic consultations in the control group. All patients were enrolled after being provided sufficient guidance with respect to discharge and health education. The health index, including the physiological function, ability to perform daily activities, and the injury response, was evaluated before and 24 hours after surgery. The time duration of each follow-up session was also evaluated in both groups. The preoperative (T1) health index scores were significantly higher than the postoperative (T0) ones in both groups ( P  = .00). The quality of recovery (T1–T0) of the intervention group (10.75 ± 5.28) was better than that of the control group (11.78 ± 5.16), but the differences were not significant ( P  = .27). In the intervention group, the follow-up time duration was significantly lower in comparison to that in the control group ( P  = .00). This study demonstrated that 317NAPP had a positive effect on recovery following day-surgery, and the time-duration for follow-up was shorter than that performed using telephonic consultation. Monitoring recovery using 317NAPP was safe, efficient, inexpensive, and relatively easy; therefore, it may help improve the recovery of patients having undergone day-surgery.